Significance of Self-Efficacy and Student Academic Stress - Ilham Khairi Siregar; Permata Sari; Mohamad Rizal Pautina; Ryan Hidayat Rafiola (Jurnal Konseling dan Pendidikan, 2022)
Academic stress is the pressure that is felt by individuals in achieving the expected goals. The phenomenon that occurs is that students are not so confident in their abilities that they cause academic stress in achieving their college goals. This study aims to obtain a picture of student self-efficacy and an overview of student academic stress in the guidance and counseling study program. Based on the results of the study found the coefficient of self-efficacy variables with student academic stress is said to be significant and negatively correlated. This research departs from the fact that many students feel pressured by many assignments at school, and this causes their stress symptoms to experience at school. Therefore the ability to solve problems (self-efficacy) is thought to be very important to deal with these problems. The purpose of this study is to examine the relationship between self-efficacy and stress symptoms of elementary school students (Madrasah Ibtidaiyah Private) in Solok City, West Sumatra. This research uses a quantitative approach, with a population of 354 students. However, only grades 4-6 were included in this study as a sample totaling 80 people. The sampling technique used is proportional to stratified soak sampling. The statistical model used in this study is the Pearson correlation. The results of this study prove the relationship between self- efficacy and stress symptoms of school students. {page:WordSection1;}